Strategic Preparation of Efficient and Durable NiCo Alloy Supported N-Doped Porous Graphene as an Oxygen Evolution Electrocatalyst: A Theoretical and Experimental Investigation - Singh, Santosh K.; Kumar, Deepak; Dhavale, Vishal M.; Pal, Sourav; Kurungot, Sreekumar (Advanced Materials Interfaces, 2016)
Development of an efficient and durable water splitting electrocatalyst holds a great commitment for the future energy devices. The real application of oxygen evolution reaction (OER) catalysts mainly suffers from sluggish kinetics and high overpotential except for the Ir and Ru-based systems. However, the high cost and vulnerability of the Ir and Ru metals are the main hostiles to use them for marketization. Herein, a high-performance OER electrocatalyst consisting of NiCo alloy nanoparticles supported on high surface area N-doped porous graphene (NiCo/pNGr(75: 25)) is reported. The importance of the doped-N for achieving the uniform dispersion-cum-effective interaction of the size controlled NiCo alloy nanoparticles has been explicitly investigated by transmission electron microscopy, X-ray diffraction, X-ray photo electron spectroscopy, Raman, density functional theory (DFT) calculations, etc. The electrochemical analysis of NiCo/pNGr(75: 25) shows an overpotential of approximate to 260 mV at 10 mA cm(-2) with a smaller Tafel slope of approximate to 87 mV dec(-1) and long catalytic durability. DFT calculations are done to check the interaction between the NiCo alloy nanoparticles and the defective sites of pNGr and also with the doped-N, which could be attained for maintaining long catalytic durability. Furthermore, NiCo/pNGr(75: 25) is used as an OER catalyst to fabricate an electrolyzer, which works at very low potential of 1.5 V in 1 M KOH.